1984
DOI: 10.1007/bf02582144
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of carbohydrate esters of fatty acid (I) esterification of sucrose, glucose, fructose and sorbitol

Abstract: The authors attempted to synthesize carbohydrate esters of fatty acids enzymatically in order to overcome the problems associated with the chemical processes for the synthesis of commercial sucrose esters. The enzymes used were lipases from microorganisms belonging to Rbyzopus, Enterbacterium, Aspergillus, Pseudomonas, Cbromobacterium, Candida, Mucor and Penicillium. Fatty acids (stearic, oleic and linoleic) and carbohydrates (sucrose, glucose, fructose and sorbitol) used for the reaction were obtained from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(44 citation statements)
references
References 15 publications
1
38
2
Order By: Relevance
“…Stearic acid, oleic acid, and linolenic acid gave 26.2%, 24.4% and 42.4% of esterification, respectively, under similar reaction conditions. Seino et al (1984) reported that linoleic acid and oleic acid yielded a higher amount of esters than stearic acid by lipase from Candida cylindracea. The lipase from B. fulva had a higher extent of specificity towards the triglycerides containing linoleic acid in an aqueous solution (Ku & Hang, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Stearic acid, oleic acid, and linolenic acid gave 26.2%, 24.4% and 42.4% of esterification, respectively, under similar reaction conditions. Seino et al (1984) reported that linoleic acid and oleic acid yielded a higher amount of esters than stearic acid by lipase from Candida cylindracea. The lipase from B. fulva had a higher extent of specificity towards the triglycerides containing linoleic acid in an aqueous solution (Ku & Hang, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Disappearance of two absorption peaks at around 1130 cm -1 and 920 cm -1 was observed. Those peaks were attributed to the glycosidic linkage (C-O-C) contribution (Kacurakova et al 2000) and pyranose ring of sucrose (Seino et al 1984). This indicated the decomposition of sucrose.…”
Section: Insoluble Matter and Ft-ir Analysismentioning
confidence: 95%
“…To obtain monoglucosylated transfer product, the solution was then treated with Aspergillus sp. glucoamylase (6,200 unit, a partially purified preparation obtained from Glucozyme NEO XL-128, Nagase Biochemicals Co.) at 40°C for 2 hr. Glc-TMP, Gal-TMP, and Frc-TMP finally isolated were 1120 mg, 699 mg, and 329 mg, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…2 -5) It has also been reported that esters of sorbitol and several carbohydrates were synthesized in aqueous reaction systems. 6,7) Specific and efficient esterification of alkyl glucosides by immobilized Candida antarctica lipase has been reported recently. 8) To improve the reactivity of carbohydrates with lipase and the selectivity of hydroxyl groups to be esterified, we synthesized several kinds of glycosides, the reducing ends of which were glycerol and 2-ethyl-2-(hydroxymethyl)-1,3-propanediol (trimethylolpropane, TMP), by enzymatic transglycosylation.…”
mentioning
confidence: 99%